Morphological changes in root dentin after irradiation with diode laser 980 nm in two directions: an in-vitro study - Elsayed Abdallah Eltayeb; Soha Adel Abdou (Journal of the Arab Society for Medical Research)
Background/aim Laser technology is an essential aid tool for endodontic treatment procedures. The most common type of laser used in the endodontic field was diode laser 980 nm. The present work aimed to assess the morphological variations and chemical changes in root canal dentin treated with diode laser 980 nm in two directions parallel and perpendicular by scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS). Materials and methods Thirty extracted human single-rooted lower premolars teeth with mature apex were chosen from Dental Department of Research Institute of Ophthalmology, Egypt. Their crowns were resected at the cement-enamel junction (CEJ), and their roots were mechanically prepared. The roots were categorized into two groups (each = 15): according to the direction of laser application. In group A the laser was directed parallel to the root canal, while in the group B it was directed perpendicular to the root canal. All groups were analyzed by SEM and EDS examination. Statistical analysis was done by Kolmogorov-Smirnov and Shapiro-Wilk tests and comparison between two groups was performed by independent t-analysis, while in qualitative data Chi-square test was used. Results The results of group A where the laser was directed parallel to the root canal exhibited score 1 (86.7%) in the coronal section, score 3 (80%) in the middle section, and score 4 (80%) in the apical section. The results of group B where the laser was directed perpendicular to the root canal represented score 1 (86.7%) in the coronal section, score 1 (73.3%) in the middle section, and score 3 (73.3%) in the apical section. Conclusion Diode laser 980 nm in a perpendicular direction to root canal dentin surface produced more morphological changes than when used in a parallel direction, however regarding the chemical changes, there were no chemical changes detected between the two directions.